Question

(821
( f(x)=e^{2 x} )
( g(x)=log sqrt{x}(x>0) )
( f_{0} g(x) )
( f(log sqrt{x}) )
( =e^{2 log sqrt{x}}=e^{log x} )
( =x^{2}+1 )
Mentuon which one

# 21. If f(x) = e2x and g(x) = log x(x>0), then fog(x) is equal to (1) 82x (2) log x (3) e2* (10gVx) (4) × 22. If f(x) = 5 2 , then (fofof )(x) = bouton (2) T3x2 3x (4) None of these 23. If g(x) = x2 + x - 2 and 1 g(f(x)) = 2x2 – 5x +2, then f(x) is (1) 2x - 3 (3) 2x2 + 3x + 1 (2) 2x + 3 (4) 2x2 – 3x - 1 2X+1 24. Let the function f be defined by f(x) = ***, then f-'(x) is 1-30 3x+2 x-1 3x +2 (2) ***? X-1 (3) 3x-2 2x+1 1-3X

Solution